America [videorecording (DVD)] : imagine the world without her - D'Souza, Dinesh, 1961-; D'Souza, Dinesh, 1961-; Sullivan, John (Filmmaker); D'Souza, Dinesh, 1961- (Lionsgate, 2014)
In an era where the American Dream seems to have faded into a dark new dawn, filmmakers Dinesh D'Souza and John Sullivan ponder what may have become of the world if the U.S. had never come into being. By creating an alternate history in which British forces kill General George Washington during the American Revolutionary War, the filmmakers lay the groundwork for a thought-provoking meditation on the crucial role of the United States on the world stage.